Business Development Strategy through Multi-Method Business Planning - Lucky Purnama; Keni Karnawati (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2026)
This study examines the strategic feasibility of reopening PT Mahaka Gemilang Mandiri’s branch in Cianjur, Indonesia, through an innovative business plan integrating localized credit restructuring, community trust, and digital innovation. Utilizing a qualitative case study design, data were triangulated from in-depth interviews, field observations, and financial records. The analytical framework synthesized SWOT, IFAS, and EFAS matrices with entrepreneurial models, including Design Thinking, the Business Model Canvas (BMC), and the Timmons Model. Findings reveal significant market opportunities in restructuring non-performing loans (NPLs) within the MSME and agrarian sectors. The proposed "hybrid trust-digital" model harmonizes personalized financial consultation with technological tools like Early Warning Systems (EWS) and Customer Relationship Management (CRM). Financial analysis confirms robust viability, with a projected net profit of IDR 329 million, a positive NPV of IDR 310 million, an IRR of 22%, and a payback period under two years. This research contributes a pioneering framework by integrating entrepreneurial orientation into the credit restructuring sector, demonstrating how socio-cultural capital and digital modernization synergize to enhance sustainable financial inclusion and regional economic resilience.